Analisis power otot tungkai dan kecepatan lari terhadap kemampuan lompat jauh - M.Pd, Sitti Maifa (Universitas Hamzanwadi, 2024)
This research is a type of descriptive research. Formulation of the problem in this research: How does leg muscle power affect long jump ability, how does running speed affect students' long jump ability, how does leg muscle power and running speed together affect long jump ability. The aim of the research is to find out how leg muscle power affects long jump ability, to find out how running speed affects long jump ability, to find out how leg muscle power and running speed together affect long jump ability. The population of all male students of SMP Negeri 1 Kotabaru Regency, 30 male students of SMP Negeri 1 Kotabaru Regency were used as samples. Random sampling technique by drawing lots. Data analysis techniques are descriptive analysis and inferential analysis using the SPSS 22.00 program with a significance level of 5% or α = 0.05. The results of the research show that: There is a contribution of leg explosive power to long jump ability of 43.9%. There is a contribution of running speed with long jump ability of 35.1%. There is a contribution of explosive leg power and running speed together with a long jump ability of 47.5%.